2018
DOI: 10.1111/gcbb.12530
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production in plantations: Land constraints increase dependency on irrigation water

Abstract: Integrated assessment model scenarios project rising deployment of biomass‐using energy systems in climate change mitigation scenarios. But there is concern that bioenergy deployment will increase competition for land and water resources and obstruct objectives such as nature protection, the preservation of carbon‐rich ecosystems, and food security. To study the relative importance of water and land availability as biophysical constraints to bioenergy deployment at a global scale, we use a process‐detailed, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…This approach enables us to highlight and quantify trade-offs regarding different levels of water protection, impacts of climate change versus mitigation through BECCS, and also the possible contribution of improved water management to help solve this dilemma. Unlike previous BECCS water demand studies 31 , 32 , we apply transient land use projections for both bioenergy and food crops 33 , which are consistent with future pathways of green-house gas emissions and socio-economic development.…”
Section: Introductionmentioning
confidence: 99%
“…This approach enables us to highlight and quantify trade-offs regarding different levels of water protection, impacts of climate change versus mitigation through BECCS, and also the possible contribution of improved water management to help solve this dilemma. Unlike previous BECCS water demand studies 31 , 32 , we apply transient land use projections for both bioenergy and food crops 33 , which are consistent with future pathways of green-house gas emissions and socio-economic development.…”
Section: Introductionmentioning
confidence: 99%
“…In general, plantations productivity is closely related to water availability (Álvares-Dávila et al, 2017;Jans et al, 2018). When trees are under drought stress situations, a decrease in stomatal conductance and photosynthetic activity occurs (Chen, 2020), resulting in a lower total dry weight, decrease in leaf area, loss of leaves or even total defoliation (Monclus et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Yamagata et al (2018) suggested 1910 km 3 yr −1 of consumptive water demand for bioenergy crops to achieve NEs of 3.3 Gt C yr −1 , while Séférian et al (2018) estimate the water demand for producing 220-270 EJ in 2100 to be only 178 km 3 yr −1 , which is probably a result of strong restriction of irrigation and model limitations. Jans et al (2018) project a demand of 1,500-5000 km 3 yr −1 to generate 200-1000 EJ, while also securing environmental flow requirements (EFRs) with the prospect of maintaining freshwater ecosystems in a good state.…”
Section: Introductionmentioning
confidence: 99%